Analisis Anggaran Pendidikan Dan Pelatihan Bagi Peningkatan Profesionalisme Guru Di Kabupaten Mamuju - Taufiq Taufiq (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2018)
The research conducted aims to obtain an overview of the education and training budget for improving the professionalism of teachers in Mamuju district, using a qualitative approach. The technique used in determining research informants is purposive sampling. The data collection was carried out with participatory observation techniques, semi-structured interviews and document review. The results of the study show that the education and training budget planning process for increasing the professionalism of teachers in Mamuju District is not yet fully ideal for implementing the five principles that are theoretically believed to be good budgeting principles in the public sector. There are many influential factors in the budget planning process, namely apparatus resources, planning documents (development and budgeting), nominative lists, budgets, and facilities (facilities and infrastructure). The education and training budget for increasing teacher professionalism in the government in the Mamuju district faces the following constraints: 1. Limited resources; 2) participant mechanisms for education and training for improving teacher professionalism; and 3) communication and coordination of related parties that are still weak. To overcome these various obstacles, interested parties have made staff review efforts to the regents, improved budgets and organized education and training for improving teacher professionalism and increasing the intensity of communication and coordination with various relevant parties.